The fatter are happier in Indonesia - Sohn, Kitae (Springer, 2017)
Â© 2016, Springer International Publishing Switzerland. Purpose: Although obesity and happiness are known to be negatively related in the developed world, little attention has been paid to this relationship in the developing world. We thus investigated the relationship in Indonesia and attempted to explain the underlying rationale. Methods: We considered about 12,000 respondents aged 15+ for each gender obtained from the Indonesian Family Life Survey 2007 by relating a measure of happiness to weight-related measures in ordered probit models. Results: The relationship between obesity and happiness was positive in Indonesia, and this relationship was robust. Our evidence suggests that the contrasting results for the two worlds result from affordability of obesity. That is, while even low socioeconomic status (SES) individuals in the developed world can afford to be obese, only high SES individuals in the developing world can do. Conclusions: Our findings imply that obesity prevention in the developing world requires different measures than those used in the developed world.